2020
DOI: 10.21203/rs.2.24323/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of gluteus medius strength between obese and eutrophic individuals: a cross-sectional study

Abstract: Background: The hip abductor muscles, primarily the gluteus medius, play an important role in stabilizing the pelvis during gait. Gluteus medius weakness is associated with biomechanical changes and musculoskeletal disorders. Obese individuals can have great difficulty maintaining abductor muscular function due to being overweight and possibly experiencing a decrease in muscle mass. However, it is still unclear whether the musculature of obese individuals can compensate for these changes. Therefore, the aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…It is possible that the long-term effect of obesity on muscle tissue overlaps with this weight stimulus on antigravity muscles and culminates in muscle loss over time. 2 Regarding muscle mass, the authors also reported that individuals with obesity required greater gluteal muscle strength for normal gait. This evidence is relevant since it suggests that individuals with obesity need stronger gluteal muscles, causing them to be more susceptible to fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the long-term effect of obesity on muscle tissue overlaps with this weight stimulus on antigravity muscles and culminates in muscle loss over time. 2 Regarding muscle mass, the authors also reported that individuals with obesity required greater gluteal muscle strength for normal gait. This evidence is relevant since it suggests that individuals with obesity need stronger gluteal muscles, causing them to be more susceptible to fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…If weight overload or muscular deterioration occurs, an adaptation of the upper body will be started in an effort to bring the centre of gravity closer to the centre of hip rotation. 2 For obese people, maintaining the strength of the gluteus musculature can be exceedingly difficult. Larger hip adduction with noticeable ankle eversion was seen during the terminal stance and per-balance phases of a three-dimensional gait examination of obese individuals.…”
Section: Introductionmentioning
confidence: 99%